PERBEDAAN KEBAHAGIAAN PADA GURU PNS DAN GURU HONORER DI MAN SIDOARJO - Hanifah Aliyah Rahmah (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Happiness is an important psychological aspect in an individual's life, including for teachers. Happiness is characterized by positive emotions, life satisfaction, and engagement in meaningful activities. Teachers with higher levels of happiness tend to perform teaching and learning activities more effectively. One factor assumed to influence happiness is economic condition. Differences in employment status between civil servant teachers and honorary teachers result in differences in income, which may affect their happiness levels. This study aimed to determine the differences in happiness levels between civil servant teachers and honorary teachers at MAN Sidoarjo. This research employed a quantitative approach involving 76 teachers, consisting of 63 civil servant teachers and 13 honorary teachers. Data were collected through questionnaires, interviews, and documentation. Data analysis was conducted using the Independent Sample t-Test with SPSS version 25. The findings revealed a significance value of 0.197 (p > 0.05), indicating that there was no significant difference in happiness levels between civil servant teachers and honorary teachers at MAN Sidoarjo. Furthermore, the happiness levels of both groups were classified in the moderate category.